Applications of Wiki in web-based research support system. Issue 1 (5th June 2020) - Au, Cheuk Hang; Ho, Kevin K.W.
Abstract : Purpose: This paper is to address the research gaps about Research Support System (RSS) as mentioned by earlier articles, and to provide a possible solution to develop an RSS for supporting academics in conducting their research. Design/methodology/approach: This study adopts a single-case study with the application of netnography. Data were collected from an ongoing-using Wiki and the data were analysed using the theoretical lens established from earlier articles. Findings: The result confirmed the possibilities of using Wiki to establish a system for supporting research. The authors have established a 3-stage EDM (Establishment, Development, Management) process model for illustrating the steps. Research limitations/implications: This single-case study revealed the possibility for using Wiki as RSS for helping academics to conduct their research through providing support in preparing literature review, conducting project management and providing an archive for research methodologies. The paper also provided suggestion for practitioners on the implementation of the RSS. Originality/value: This paper presents one of the earliest studies for developing a model to explain how to develop an RSS that gives a more concrete definition of RSS and outline a process of using Wiki as an RSS.